2014
DOI: 10.1111/trf.12891
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a new apheresis device for automated red blood cell exchange procedures in patients with sickle cell disease

Abstract: The SO performed effectively and safely for both the RBCX procedure and the RBCX depletion/exchange procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 21 publications
1
28
0
3
Order By: Relevance
“…In a series of 75 RBCX sessions performed with the SO device in 72 patients, Quirolo et al observed a higher AE rate with the depletion protocol (22.7%) than without (16.0%). However, this discrepancy can be explained by the different designs of the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of 75 RBCX sessions performed with the SO device in 72 patients, Quirolo et al observed a higher AE rate with the depletion protocol (22.7%) than without (16.0%). However, this discrepancy can be explained by the different designs of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the performances of the SO device when using the RBCX technique associated (SO/DE) or not (SO) with the depletion step for patients with SCA . These studies showed similar performance of SO compared to CSP both associated and not associated with DE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The EAC focussed on results from the six comparative studies with manual RBC exchange [18–23] because these provided the most useful data relevant to the decision problem, and the peer-reviewed single-armed studies of the Spectra Optia [28] and Cobe Spectra systems [24, 26, 27, 29, 30], as these studies were fully reported and provided useful supporting data. Details of these studies are summarised in Table 1.…”
Section: Review Of Clinical Effectiveness Evidencementioning
confidence: 99%
“…No analytical data reported Masera et al [27], retrospective data review, ItalyChildren with SCD ( n  = 34) at high risk for vaso-occlusive complicationsCobe SpectraMedium methodological quality but poorly reported. Results poorly generalisable Quirolo et al [28], retrospective observational study, USAAdults and older children with SCD ( n  = 60)I: Spectra OptiaC: Spectra Optia (dRBCx)(Subgroup analysis)High quality with good reporting. Key paper in determining Spectra Optia resource use Sarode et al [29], retrospective observational study, USAAdults with SCA ( n  = 20), stable with history of thrombotic strokeI: Cobe Spectra (dRBCx)C: Cobe Spectra (standard)(Historic controls)Medium methodology with good reporting.…”
Section: Review Of Clinical Effectiveness Evidencementioning
confidence: 99%